VRI4WD UFPR-MAP: A Multi-Sensor Dataset with Geodetic Ground-Truth for Wheeled Mobile Robots in Hybrid Environment - Magrin, Carlos Eduardo; Bombardelli, Felipe Gustavo; Cruz, Wander da; Todt, Eduardo (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2025: Anais do XVII Simpósio Brasileiro de Robótica e XVI Workshop de Robótica na Educação, 2025)
This paper presents the UFPR-MAP dataset, collected with the VRI4WD mobile robot platform equipped with diverse low-cost sensors, including GNSS, laser scanner, IMU, ultrasound, infrared, encoders, and WLAN signal receivers. Unlike high-end datasets, UFPR-MAP focuses on affordable sensor blend sets for indoor and outdoor environments, validated through rigorous ground-truth via GNSS and total station measurements. The dataset supports research on multi-sensor fusion and wheeled mobile robot localization in varied architectural contexts. The VRI4WD UFPR-MAP dataset is available in https://github.com/VRI-UFPR/ufpr-map .